Cosmopolitanism and Neo-Stoicism, Today - Prudencio, José Javier Benéitez (Pensamiento. Revista de Investigación e Información Filosófica, 2014)
The most famous legacy of classic Stoicism to modern thought are the notion of natural law and the related conception of cosmopolitanism. These Stoic ideas are the most influential in the entire Western tradition, although they have been transformed by new historical, political and ideological circumstances. This process of appropriation continues to this day. Martha Nussbaum, among contemporary philosophers, rearticulates one of the most distinguished and valuable theories that explicitly follow a Stoic or Neo-stoic approach. My purpose in this paper is to analyze her exposition on world citizen ship rather than the later critical discussions which usually arise from Nussbaum´s consideration about groupings such as family, ethnicity, nation, or class which are contingent barriers between us and our fellow human beings.
Keywords: Cosmopolitanism; citizenship; Neo-stoic thought; M. C. Nussbaum